Magnetization Behavior of Co Nanodot Array - 장준연; B. A. Gribkov; HyungJun Kim; 구현철; 한석희; V. L. Mironov; A. A. Fraerman (한국자기학회, 2007)
We performed magnetic force microscopy (MFM) observation on array of Co dots in order to understand magnetic state and magnetization behavior of submicron sized Co dots patterned on GaMnAs bridge. MFM observations showed the magnetization reversal and processes of local magnetization of individual ferromagnetic Co nanodots. Magnetic state of Co dots either single domain or vortex is dependent on geometrical size and thickness. Transition from single domain to vortex state can be realized with MFM tip assisted local field. Magnetization reversal process takes place through sequential reversal of individual dots. Localized inhomogeneous magnetic field can be manipulated by controlling magnetic state of individual Co dot in the array structure.